REVIEW ARTIKEL: SKIRINING FITOKIMIA DAN AKTIVITAS FARMAKOLOGIS TANAMAN KRATOM (Mitragyna speciosa Korth) - Aina, Nur; Saleh, Chairul; Marliana, Eva (PROSIDING SEMINAR KIMIA, 2024)
Kratom (Mitragyna speciosa korth) is one of the plants found in forest areas in Indonesia. Phytochemical screening and pharmacological activity of kratom plants (Mitragyna speciosa Korth) have been conducted. Some studies show kratom plants contain secondary metabolites, namely alkaloids, flavonoids, saponins, triterpenoids, tannins and terpenoid-steroids. Literature studies show kratom leaves have strong antioxidant activity with IC50 values <50 ppm. Kratom leaves have antinonceptive activity in the dichloromethane fraction at doses of 70 mg/kgBB (51%), 140 mg/kgBB (81%) and 280 mg/kgBB (86%). Antimicrobial activity against staphylococcuc pidermidis bacteria with a concentration of 5% (7.23 mm) 10% (10.50 mm), 15% (11.78 mm), 20% (12.63 mm) and 25% (13.69 mm). Stems and roots of kratom plants have antibacterial activity against propionibacterium acnes bacteria, stem concentration 5% (5.71 mm ± 0.40), 10% (6.75 mm ± 0.26) and 15% (6.78mm ± 0.29), on roots 5% (5.4 mm ± 0.12), 10% (5.8 ± 0.08) and 15% (6.21 mm ± 0.36). Anti-inflammatory activity with a dose of kratom extract 0.5 mg/grBB (46.37 mm ± 10.04), 1 mg/grBB (32.33 mm ± 11.24), 2mg/grBB (26.69 mm ± 6.57). Acute toxicity test in the reflux method LC50 value of 71.08 ppm while the maceration method LC50 value of 143, 50 the results shown are included in the toxic category. Keywords: Mitragyna speciosa korth, Mitragyna, phytochemical screening